P02.05.B Targeted therapies of Glioblastoma using single cell sequencing and drug-response analysis in a phase 2 clinical trial setting. (5th September 2022) - Lü, M; Hendriksen, J; Urup, T; Hamerlik, P; Wennerberg, K; Lassen, U; Skovgaard, H; Weischenfeldt, J
Abstract: Background: Glioblastoma is an aggressive brain tumour with a median survival of less than 15 months despite aggressive standard treatment consisting of neurosurgery, radiotherapy plus concomitant and adjuvant chemotherapy with temozolomide. There is no standard treatment at recurrence, and all have limited efficacy. In this study we will enroll glioblastoma patients from the Danish clinical trial "Protarget" to get a better understanding of resistance mechanisms and vulnerabilities in glioblastoma to give personalized medicine to glioblastoma patients at recurrent disease. We hypothesise that two connected factors are responsible for the failure to successfully target glioblastoma: i) intra-tumour heterogeneity and within this ii) cancer stem cells. Material and Methods: We will use tumour tissue from glioblastoma patients included in the Danish phase 2, prospective, non-randomized clinical trial "Protarget" to establish short-term cultured neurospheres to preserve the heterogeneity of the tumour including cancer stem cells. We will then perform single cell RNA sequencing before and after drug screening. This setup will allow for a new approach to identify drug vulnerabilities at the single cell level. If successful in identifying drugs that leads to a clinical response, according to the "ProTarget" guidelines, we will consider scaling up the effort, to allow broader evaluation of efficacy. Our plan is to enroll 10 patients as a start. Patients will be selected based on ProTarget inclusion criteria and molecular profiling. We will further select patients with the following characteristics:1. IDH wildtype 2. High tumour purity (>50%). 3. High degree of intra-tumour heterogeneity. Results: Enrollment for "Protarget" began in 2020 and our cohort will be part of this study, which is why enrollment has already started, but the first patient has not been enrolled yet. Clinical trial registry number for "Protarget" is NCT04341181. Conclusion: This new and flexible approach to identify drug vulnerabilities at the single cell level in glioblastoma in order to find targeted therapies is a promising tool for future treatment of glioblastoma patients.